Emigración de padres y madres, manejo sociofamiliar e implicaciones para hijos e hijas menores. / Emigration of Fathers and Mothers, Socio-familial Handling and Implications for Minor Children. - Consuelo Martín Fernández; Patricia Arés Muzio (Universidad de La Habana, 2021)
The dynamic of the relations between family and migrations have been studied in Cuba, but demand more depth in their multiples and complex dimensions. This article presents the systematization of the experience of many years of work (2005-2019) attending families in clinical Psychology, because of the emigration of fathers or mothers of minor sons and daughters who stay in the country of origin. Objectives: to describe the socio-familial handling of the emigration of fathers and mothers; and to evaluate the psychological consequences that generate over minor sons and daughters. Qualitative methodology of research throw out phenomenological method. Conclusive results: the socio-familial handling of the emigration of parental figures complex the family dynamics and increase their quotidian conflicts. The caretakers approach the situation from questionings and "silences", with a tendency to the "emotional erase" of emigrated parental figure, despite of their assumed presence throw out the online communication ways. The emotional response that characterize the minors is the aggressiveness against themselves or towards others, specially linked to familial area. The future uncertainty, anxiety, and anguish are frequent expressions of psychological implications in minors. The category socio-familial handling of the emigration of fathers and mothers is newfangled and actual; contribute to the clinical practice of psychological attention to minors in migratory context; offer another comprehension from an interdisciplinary psychosocial approach of the social sciences; and support the infancy institutional management in the society. / RESUMEN La dinámica de las relaciones entre familia y migraciones ha sido estudiada en Cuba, pero reclama mayor profundización en sus múltiples y complejas dimensiones. Este artículo presenta la sistematización de la experiencia de varios años de trabajo (2005-2019) en la asistencia a familias que llegan a consulta de Psicología, debido a la emigración de padres o madres de hijos e hijas menores que quedan en el país de origen. Objetivos: describir el manejo sociofamiliar de la emigración de padres y madres; y evaluar las consecuencias psicológicas que genera en los hijos e hijas menores. Metodología de investigación cualitativa a través del método fenomenológico. Resultados conclusivos: el manejo sociofamiliar de la emigración de figuras parentales complejiza las dinámicas familiares y agrava sus conflictos cotidianos. Los cuidadores abordan la situación desde cuestionamientos y "silencios", con una tendencia al "borramiento emocional" de la figura emigrada, a pesar de su supuesta presencia a través de las vías de comunicación online. La respuesta emocional que caracteriza a los menores es de agresividad hacia sí mismos o hacia los demás, especialmente vinculada al área familiar. La incertidumbre sobre el futuro, la ansiedad y angustia son frecuente expresión de implicaciones psicológicas en los menores. La categoría manejo sociofamiliar de la emigración de padres y madres es novedosa y actual; contribuye a la práctica clínica en la atención psicológica a menores en contexto de migraciones; ofrece una comprensión desde un enfoque psicosocial interdisciplinario de las ciencias sociales; y apoya la gestión institucional de la infancia en la sociedad.